ANALISIS STRUKUR KALIMAT TEKS BERITA “DINKES DKI :PASIEN GANGGUAN GINJAL AKUT BANYAK YANG MENINGGAL KARENA TERLAMBAT TERDIAGONIS” PADA KOMPAS.COM TERBITAN 22 OKTOBER 2022, 21:30 WIB - Nur Wulida Muslimah; Sri Ratna Erlina (Universitas Maritim AMNI Semarang, 2022)
The purpose of this study is (1) to describe the errors in terms of syntax, which are found in online media Kompas.com; (2) to provide correction of language errors in terms of syntax, which are contained in Kompas.com online media. This research is a descriptive qualitative research. The data collection technique used is the listening technique to obtain data by listening to the use of language and note-taking techniques to record words or sentences for analysis. The results of the analysis regarding the analysis of language errors can be concluded that there are forms of language errors in the field of syntax. One of them is the researcher determines the structure of sentences in news texts based on functions, categories, and roles.